Development,challenge and opportunity of optical fiber communication system technologies - Xiuguo CUI; Xiang LIU; Shiyi CAO; Min ZHOU (Dianxin kexue)
Optical fiber communication system is one of the core supporting systems of the modern internet age.Firstly,major recent technological advances in optical fiber communication system were summarized.Then,the driving forces for its future development in the emerging cloud era,the future challenges and opportunities that it faced were analyzed.With the consideration of these challenges and opportunities,the future evolution paths in key areas such as optical fiber communication system overall network architectures,core network technologies,metro network technologies,access network technologiesand novel software-defined optical transport network technologies in the upcoming cloud erawere described,aiming to support future generations of internet,data center interconnect,internet of things and 5G mobile network,as well as the smart home and smart city initiativesmore effectively.